Asymmetrical benzo[a]-fused N2O2-boron-chelated BODIPYs as red to near-infrared absorbing chromophores: synthesis, characteristics and device applications for opto-electronics. Issue 3 (22nd January 2021) - Kubo, Yuji; Nozawa, Toshiki; Maeda, Kentaro; Hashimoto, Yuta
Abstract : Asymmetric benzo[ a ]-fused BODIPYs with benzo(thieno)[1, 3, 2]oxazaborinine units 1–4 were synthesized, not only the relationship between the structure and photophysical properties but also a potential device application being investigated. Abstract : Asymmetric benzo[ a ]-fused BODIPYs with benzo(thieno)[1, 3, 2]oxazaborinine units 1–4 were synthesized for the first time. The structural feature was elucidated by X-ray crystallography and NICS(0) calculation, indicating that the isoindole ring may possess azafulvene character. The photophysical properties of the dyes were investigated, demonstrating that they absorb far-red and NIR light with a λ max value of 663–709 nm in THF. Replacement of benzo[1, 3, 2]oxazaborinine with the thieno-counterpart caused a red-shift in the absorption band. Interestingly, the effect of thiophene insertion on the photophysical properties is dependent on the position of the thiophene in the chromophore, as determined from cyclic voltammetry (CV) measurement and theoretical calculations. Further, N2 O2 -ligated sp 3 -boron induces chirality into the chromophore, facilitating optical resolution of 2 by chiral high-pressure liquid chromatography; helical dyes P -2 and M -2 were successfully characterized. As a potential device application, a single component device (ITO/dye 2 /Al) was fabricated to produce a photocurrent of 8.42 × 10 −7 A cm −2 at a bias potential of 1 V under photoirradiation at 750 nm (128 μW cm −2 ). Compared to the dark current, the on/off current ratio at the same bias potential was determined to be 1.42 × 10 2 . The result suggests that a sophisticated combination of asymmetrical BODIPY with a n-type acceptor would allow for NIR photodiodes with a p–n interface.